Generalized Connes-Chern characters in KK-theory with an application to weak invariants of topological insulators - Prodan, Emil; Schulz-Baldes, Hermann (Reviews in Mathematical Physics, 2016)
We use constructive bounded Kasparov K" role="presentation">K-theory to investigate the numerical invariants stemming from the internal Kasparov products Ki(풜)×KKi(풜,ℬ)→K0(ℬ)→ℝ" role="presentation">Ki(𝒜)×KKi(𝒜,ℬ)→K0(ℬ)→ℝ, i=0,1" role="presentation">i=0,1, where the last morphism is provided by a tracial state. For the class of properly defined finitely-summable Kasparov (풜,ℬ)" role="presentation">(𝒜,ℬ)-cycles, the invariants are given by the pairing of K" role="presentation">K-theory of ℬ" role="presentation">ℬ with an element of the periodic cyclic cohomology of ℬ" role="presentation">ℬ, which we call the generalized Connes–Chern character. When 풜" role="presentation">𝒜 is a twisted crossed product of ℬ" role="presentation">ℬ by ℤk" role="presentation">ℤk, 풜=ℬ⋊ξθℤk" role="presentation">𝒜=ℬ⋊θξℤk, we derive a local formula for the character corresponding to the fundamental class of a properly defined Dirac cycle. Furthermore, when ℬ=C(Ω)⋊ξ′ϕℤj" role="presentation">ℬ=C(Ω)⋊ϕξ′ℤj, with C(Ω)" role="presentation">C(Ω) the algebra of continuous functions over a disorder configuration space, we show that the numerical invariants are connected to the weak topological invariants of the complex classes of topological insulators, defined in the physics literature. The end products are generalized index theorems for these weak invariants, which enable us to predict the range of the invariants and to identify regimes of strong disorder in which the invariants remain stable. The latter will be reported in a subsequent publicatio
Keywords: Operator Algebras; Disordered Systems and Neural Networks; Mathematical Physics; K-Theory and Homology